Analisis Efisiensi dan Efektivitas Pengelolaan Keuangan Daerah Kota Sorong Tahun Anggaran 2013-2018. - Bambang Sunatar; Arfandi SN (At-Thariqah: Jurnal Ekonomi, 2021)
The aim of this research is to analyze the level of efficiency and effectiveness of regional financial management in Sorong City for the 2013-2018 Fiscal Year. In this research, the researcher used a type of research with descriptive quantitative analysis methods (Descriptive). The sample in this research was the Sorong City Government Financial Report, using time series data for 5 (five) years, namely from 2013 to In 2018, the object studied was the Sorong City Regional Government Budget Realization report regarding Balancing Funds, Original Regional Income (PAD), Expenditures and Financing. The research results showed that the pattern of development of the level of efficiency of regional financial management in the Sorong City Government during 2013-2018 tended to remain less, the results of the analysis show that the calculation using the formulation of the level of efficiency of regional financial management for the Sorong City Government during 2013-2018 on average is the Fiscal Decentralization Degree Ratio for the 2013-2018 Fiscal Year with results based on an average level of 11.36%. The development pattern of the level of effectiveness of regional financial management in the Sorong City Government during 2013-2018 tends to decline, from the results of the Sorong City Government Regional Original Income Effectiveness Ratio with the average effectiveness ratio for the Sorong City Government being around 68.02% with the criteria being less effective